The management towards organizational change: The situation of retail shops - Martínez-Daza, Magda Alejandra (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The purpose of this work is to reconstruct the administrative management of the owners (shopkeepers) of MSMEs (neighborhood shops), in the sector of the retail market in Colombia. A qualitative methodology based on participatory action research was used in three phases: diagnosis; selection of data collection techniques and fieldwork. It was revealed that "retail shops" need to employ value chain development strategies. These generate favorable supplier-grocer agreements to acquire products and services at better prices. This is how they benefit the business towards sustained and uninterrupted growth. Likewise, the final consumer.